2021
DOI: 10.1371/journal.pgen.1009391
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for Dun1 in the regulation of origin firing upon hyper-acetylation of H3K56

Abstract: During DNA replication newly synthesized histones are incorporated into the chromatin of the replicating sister chromatids. In the yeast Saccharomyces cerevisiae new histone H3 molecules are acetylated at lysine 56. This modification is carefully regulated during the cell cycle, and any disruption of this process is a source of genomic instability. Here we show that the protein kinase Dun1 is necessary in order to maintain viability in the absence of the histone deacetylases Hst3 and Hst4, which remove the ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 70 publications
5
11
0
Order By: Relevance
“…Another striking role of Ctf18 is its phenotype in response to hyper-acetylation of histones [77]. Histone deposition on newly synthesized DNA is a complicated mechanism controlled and regulated by histone modification, mainly H3K56Ac in yeast cells [78,79].…”
Section: Ctf18mentioning
confidence: 99%
See 1 more Smart Citation
“…Another striking role of Ctf18 is its phenotype in response to hyper-acetylation of histones [77]. Histone deposition on newly synthesized DNA is a complicated mechanism controlled and regulated by histone modification, mainly H3K56Ac in yeast cells [78,79].…”
Section: Ctf18mentioning
confidence: 99%
“…Interestingly, deleting any RLCs major subunits on the background of hst3∆ hst4∆ suppresses the TS phenotype of this strain [82]. However, only deletion of CTF18 suppresses the lethality of dun1∆ in the hst3∆ hst4∆ background [77]. Dun1 is a protein kinase that acts in the DDR after being activated by phosphorylation by the checkpoint kinase Rad53.…”
Section: Ctf18mentioning
confidence: 99%
“…Recently it was shown that hyper-acetylation of H3K56 affects the dynamics of the overall replication, by affecting firing of origins. In the presence of hyper-acetylation, there is constant activation of Rad53, which must be counteracted by the Dun1 checkpoint protein kinase for cells to survive [58]. The activation of Rad53 by the hyper-acetylated state of the chromatin (which is discussed extensively below in the context of checkpoint activation) causes Rad53 to inhibit late firing origins, and this in turn forces forks to traverse longer distances in order to complete genome duplication.…”
Section: Hyper-acetylation and Replicationmentioning
confidence: 99%
“…Rrm3 is a helicase that travels with the fork and is required for the replisome to pass through protein-DNA complexes [62]. Deletion of Rrm3 was found to suppress the TS phenotype of hst3 hst4 [58]. However, mutations in the acetylation machinery (Asf1, Rtt109, Rtt101, Mms1, and Mms22) together with deletion of Rrm3 are all lethal [63].…”
Section: Hyper-acetylation and Replicationmentioning
confidence: 99%
See 1 more Smart Citation